AN AUDIT OF PRIMARY POST PARTUM HAEMORRHAGE - Bibi, Shamshad; Danish, Nargis; Fawad, Anisa; Jamil, Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Postpartum haemorrhage (PPH) is one of the leading causes of maternal morbidity and mortality .Its causes & risk factors are important for its prevention and management. Poor, unhealthy, high parity women delivering away from health facility are usual victims. The purpose of this study is to determine causes of PPH, risk factors, preventable factors and to assess treatment measures adopted. Methods: This retrospective study is carried out in Gynaecology ’B’ unit of Ayub Teaching Hospital Abbottabad. All patients admitted with PPH or developed PPH within hospital from 1st Jan-31st Dec 2006 are included. Exclusion criteria were patients with bleeding disorders and on anticoagulants. Records of admissions, deliveries, caesareans, major & minor procedures and history charts were thoroughly evaluated for details. Details included age, parity, socioeconomic status, transportation facility, distance from hospital, onset of labours, birth attendant skilled/unskilled, evaluation of risk factors, duration of labour and mode of delivery. Patient’s general health, anaemia, shock, abdominal and pelvic examination and laboratory findings were also taken in to account. Treatment measures including medical, surgical, blood transfusions were evaluated. Results: The most important cause was uterine atony, 96 (70.5%) and traumatic lesions of genital tract, 40 (29.4%). Factors causing uterine atony were augmented labour 20 (20.9%), prolonged labour 21 (21.9%), retained placental tissues, 11 (12.5%), retained placenta, 11 (11.4%) Couvelliar uterus, 10 (10.4%), placenta preavia, 8 (8.3%), placenta increta, 7 (7.3%), chorioamnionitis 5 (5.2%), and multiple pregnancy, 2 (2.1%). Risk factors, grand multiparity 70 (51.5%), antepartum haemorrhage 12 (8.9%), instrumental delivery 10(7.3%), previous PPH, 6 (4.5%), choreoamnionitis, 5 (3.6%), multiple pregnancy, 2 (1.5%), no risk factor, 21 (15.4%). Socioeconomic status was poor (75) & lower middle class (61). Induced labour, 33 (24.3%), augmented labour 62 (45.5%).Uterotonics used for prophylaxis in 30 (22%), for treatment of PPH, 106 (78%). Patients delivered by traditional birth attendants 70 (51.4%), lady health workers 40 (29.4%) & doctors 26 (19.2%).Uterine massage performed in 30 (22%), minor surgical procedures 33 (24.3%), manual removal of retained placenta, 11 (8%), hysterectomy, 50 (36.7%), & compression sutures were applied in 3 (2.2%). Maternal deaths due to PPH were 6 (40%). Conclusions: PPH can be prevented by avoiding unnecessary inductions/augmentations of labour, risk factors assessment and active management of 3rd stage of labour. It needs critical judgment, early referral and early resuscitation by birth attendant. There is room for temponade and compression sutures. Hysterectomy should be the last option. Keywords: Post Partum Haemorrhage, Uterine atony, Uterotonics, Compression sutures.